Caractériser l’étendue des résistances locales aux indicateurs de performance des services d’eau. Le cas de l’agglomération grenobloise - Antoine Brochet; Thomas Bolognesi; Yvan Renou (Développement Durable et Territoires)
This article highlights the transforming dynamics that occur with the adoption of performance indicators in France. It shows an emergence of "resistances", which impedes the effectiveness of this new regulation design. We propose an original typology to open the black box of the resistances aiming at understanding their diversity. We apply the typology on the territory of the Grenoble area. Results reveal the strong impact of these resistances on the filling of the performance indicators as well as the variety of causes of these resistances and the identification of three types of services profile. We conclude by inquiring the causes of the partial failure in implementing this new public policy tool and its future potential.